Parásitos intestinales y bacterias enteropatógenas en niños de edad escolar de Maracaibo, Venezuela - Gómez-Gamboa Liliana; Velasco Vanessa; Villasmil Jessica; Ginestre Messaria; Bermúdez-González José; Perozo-Mena Armindo; Rivero Zulbey (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2018)
Abstract: Intestinal pathogens infection represents a global public health problem, and are associated with morbidity and mortality high rates, particularly in children; we determined the relative frequency of intestinal parasites and diarrheagenic bacteria in 22 children of the Basic State School "Comandante Remigio Negron", Maracaibo, Venezuela. Most of the children showed elevated parasites (72.73%) and polyparasitism (22.73%). The highest frequency corresponded to the protozoa and chromist (95.65%), finding a high frequency of Blastocystis sp. (52.17%); while Giardia intestinalis was detected only in 8.70%, in contrast to global data that indicate it is the most frequent protozoan species in children. In addition, the complex E. histolytica/E. dispar / E. moshkovskii (13.04%) was detected and also Hymenolepis nana (4.35%). Non-typhoidal Salmonella (4.54%) was also detected, the most common bacterial pathogen causing foodborne infection globally and the main stool-isolated bacteria in pediatric patients of the region. These results demonstrate the high relative frequency of intestinal parasites in the studied children, with predominance of protozoa and chromist, as well as the presence of Salmonella sp.; highlighting the need to promote the hygiene and environmental sanitation, to reduce the relative frequency of intestinal pathogens and their consequences to health and school performance. Resumen: Las infecciones por patógenos intestinales representan un problema de salud pública mundial y se encuentran asociadas con elevadas tasas de morbilidad y mortalidad, especialmente en niños; por lo cual se determinó la frecuencia relativa de parásitos intestinales y bacterias enteropatógenas entre 22 niños de la Escuela Básica Estadal "Comandante Remigio Negrón", Maracaibo, Venezuela. La mayoría de los niños presentaron parásitos (72,73%) y poliparasitismo elevado (22,73%). La frecuencia más alta correspondió a los protozoarios y cromistas (95,65%), encontrando una elevada frecuencia de Blastocystis sp. (52,17%); mientras que G. intestinalis fue detectada sólo en 8,70%, a diferencia de datos mundiales que indican es la especie de protozoario más frecuente en niños. Asimismo, se detectó el Complejo E. histolytica/E. dispar/E. moshkovskii (13,04%) e Hymenolepis nana (4,35%). Se detectó Salmonella no tifoidea (4,54%), que constituye el principal patógeno bacteriano que ocasiona infecciones transmitidas por alimentos a nivel mundial y la principal bacteria aislada de heces en pacientes pediátricos de la región. Estos resultados demuestran la elevada frecuencia relativa de parásitos intestinales en la población infantil estudiada, con predominio de protozoos y cromistas, así como la presencia de Salmonella sp.; señalando la necesidad de fomentar los hábitos higiénicos y el saneamiento ambiental, para disminuir la frecuencia relativa de patógenos intestinales y sus secuelas en el estado de salud y rendimiento escolar.